Utilization of digital media in Indonesian language learning at the Universitas Pejuang Republik Indonesia: Opportunities and challenges - Rahmatia, Andi (Universitas Jambi, Indonesia, 2026)
This research explored the use of digital media in Indonesian language learning at the Universitas Pejuang Republik Indonesia (UPRI), focusing on both the opportunities and challenges. It used descriptive qualitative methods, which involved in-depth interviews with lecturers and students, participant observation, and document analysis. The findings reveal that digital media, including e-learning platforms, interactive videos, and language learning apps, have enhanced access to materials, increased learning flexibility, and created more engaging experiences. However, the research identified challenges, including inadequate technological infrastructure, limited digital literacy, and pedagogical hurdles to maintaining humanistic interactions. Furthermore, online learning tends to reduce student focus and active participation, requiring strategies like microlearning, gamification, and collaboration to boost motivation. The research emphasizes the need for a blended learning model that combines digital tools and face-to-face interactions, along with targeted training for both lecturers and students to optimize the use of digital media. This research provides valuable insights into developing digital language-learning strategies in higher education.